THE EFFECT OF DIFFERENT FEED TYPES ON THE SURVIVAL OF CATFISH FRY (Clarias sp.) - Gabriel Victor Yudha Pranat; Anna Heirina; Sri Murtini; Neksidin Neksidin (Universitas Mataram, 2025)
Catfish have strong endurance, but until now there has been no definite alternative feed so farmers tend to spend quite a lot of capital when raising seeds. This study aims to describe the right type of feed to increase the survival of catfish seeds. The research method used is a completely randomized design (CRD) with four treatments and three repetitions, In this study, the provision of feed as a treatment and measurement of weight, length, and survival as a repetition every 7 days. Data analysis conducted in this study is an experimental method. The results of this study indicate that the absolute growth rate of catfish seeds can be supported by providing silk worm feed. This result is evidenced by acquiring an absolute length value of 0.42 mm. The growth of the absolute weight of catfish seeds can be supported by providing egg yolk feed. This result is evidenced by acquiring an absolute weight value of 24 grams. The survival rate of catfish seeds can be maintained by providing Artemia sp. feed because the results of the study showed that this feed was able to maintain the survival rate of catfish seeds at a percentage of 98%.